Optimizing Special Job Fairs in the Tracer Study of Public Vocational High School - Handayani, Endang Ary; Elmunsyah, Hakkun; Widiyanti, Widiyanti; Ying, Goh Yin (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
The paper aims to describe the effort to optimize special job fairs in the tracer study conducted by Public Vocational High School (PVHS). This was a literature review using the content analysis method, in which the researcher reviewed some research and studies published in both national and international journals and other written works relevant to the topic of this article, namely optimalizing Special Job Fairs in VET tracer studies. The result of the review showed that the unemployment rate of VHS graduates was higher than that of other educational institutions. One of the causal factors behind this poor condition was the fact that those graduates had difficulty making steps in building their career after graduation. This suggested the need for the optimization of special job fairs as events held to provide strategic direction and illustration of what VHS students should do after graduation. The tracer study under discussion in this article dealt with the distribution of students working in Business and Industrial World